2018
DOI: 10.1186/s12902-018-0262-2
|View full text |Cite
|
Sign up to set email alerts
|

General health status in Iranian diabetic patients assessed by short-form-36 questionnaire: a systematic review and meta-analysis

Abstract: BackgroundDiabetes mellitus is one of the most prevalent diseases worldwide. Diabetes is a chronic disease associated with micro- and macro-vascular complications and deterioration in general health status. Therefore, the aim of this study was to estimate general health status among Iranian diabetic patients through a systematic review and meta-analysis of study utilizing the Short-Form-36 questionnaire.MethodsSearching the EMBASE, PubMed, ISI/Web of Sciences (WOS), MEDLINE via Ovid, PsycoINFO, as well as Iran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…SF-36 is an instrument for assessment in health status. It has been confirmed that the diabetic patients were with a lower score of SF-36 [ 29 ]. We found that the patients in the study group were with a lower score of NDI and higher score of SF-36 compared to the control group, manifesting neck dysfunction, and quality of life was improved after treatment of wrist-ankle acupuncture-moxibustion and hot compression with Chinese herbal medicine.…”
Section: Discussionmentioning
confidence: 95%
“…SF-36 is an instrument for assessment in health status. It has been confirmed that the diabetic patients were with a lower score of SF-36 [ 29 ]. We found that the patients in the study group were with a lower score of NDI and higher score of SF-36 compared to the control group, manifesting neck dysfunction, and quality of life was improved after treatment of wrist-ankle acupuncture-moxibustion and hot compression with Chinese herbal medicine.…”
Section: Discussionmentioning
confidence: 95%
“…Based on the results of previous studies, Iranian patients with type 2 diabetes were not entirely satisfied with the health-care services provided, and suffered from irreversible complications that were partly due to defects in their health care 32,33,44–46. The existence of a standard tool to identify the extent of support provided by HCPs for patients with type 2 diabetes could help these patients and contribute toward the effective implementation and impact evaluation of intervention programs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that Iranian patients with diabetes generally do not receive the required quality of services. A part of this perceived deficiency may be associated with the health-care provision facilities and the overall perceived performance environment in the health-care centers 32,33…”
Section: Introductionmentioning
confidence: 99%
“…The survey instrument comprised several components: demographic information including year of birth, gender, height and weight, educational attainment, employment status, marital status, residency, income, religious a liation, medical history, and exercise frequency; an evaluation of self-perceived health status; an assessment of medication adherence via two selected items from the MMAS-8 [19]; a quality of life scale comprising six chosen items from the SF-36 [20], encapsulating three life quality domains: environmental, physiological, and social relationship; medical consultation preferences and experiences assessed via seven questions, including habits of collating information for consultations, frequency of online health issue consultations, tendencies to make consultation appointments, consultation preferences and the extent to which these preferences are ful lled (adapted from the report by Richard Baker [21]); a query concerning the presence or absence of a familiar physician; and a 5-point continuity of care scale featuring 13 items taken from the Patient Care Continuity Questionnaire (PCCQ) [22], covering three dimensions of continuity: informational (6 items), management (3 items), and relational continuity (4 items).…”
Section: Survey Instrumentmentioning
confidence: 99%
“…2). To facilitate further analyses, the quality of life scores were categorized into high (>24), medium (19)(20)(21)(22)(23)(24), and low (<19) groups, according to the 25% and 75% quartiles.…”
Section: Basic Demographic Pro Lementioning
confidence: 99%